+0  
 
0
37
1
avatar

y = -(2 - x)(x + 3)

y = (-x + 2)(5 - x) - 2x^2

 

How would they look without brackets and as short as possible?

Guest Nov 20, 2018

Best Answer 

 #1
avatar+14579 
+2

y = (-2+x)((x+3)

      (x-2)(x+3)

       x^2 +x -6

 

 

y= (-x+2)(5-x) - 2x^2

  = -5x +x^2 +10 -2x -2x^2

   = -x^2 - 7x +10

ElectricPavlov  Nov 20, 2018
 #1
avatar+14579 
+2
Best Answer

y = (-2+x)((x+3)

      (x-2)(x+3)

       x^2 +x -6

 

 

y= (-x+2)(5-x) - 2x^2

  = -5x +x^2 +10 -2x -2x^2

   = -x^2 - 7x +10

ElectricPavlov  Nov 20, 2018

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.